Assesment of Nursing Students and Clinial Nurses\' Attitude Toward Elderly Care - A. Hosseini Seresht; F. Nasiri Ziba; A. Kermani; F. Hosseini (Iran University of Medical Sciences, 2006)
Generally, increased number of old people is because of increased life expectancy. This large group of population in communities with regard to their physiological and psychological needs, necessitate special care by positive attitude from health care providers towards them. In fact, the attitude of nurses as health professionals will affect their assessing of old patients is prominent.   The aim of the study was to determine nursing students and clinical nurses' attitude toward elderly patients care.   This study was a comparative descriptive design in which a self-report questionnaire was used as data collection tool.   Through continues sampling method, 522 subjects participated in this study.   The study results revealed that there were significant differences of attitude toward old patients care between the first and third year nursing students and clinical nurses (P=0.000, c 2 =182.13). Besides, clinical nurses had positive attitude and nursing students had neutral attitude toward old patient care (P=0.000, F=149.94). In other words, the mean scores of attitude toward old patient care among clinical nurses was the highest and in the first year students was the lowest, score. Also, there were positive relationships between attitude toward old patient care and the time period of nursing employment (up to 15 years) in clinical nurses, and living with an old relative in the first year students. Moreover, female nurses had more positive attitudes toward old patients care than male nurses. According to the study findings, an extensive plan to improve nurses' attitude toward old patients is recommended. The researchers suggest that intervention to promote positive attitude in nursing, would be possible by implementing different strategies including curriculm revision.